2020
DOI: 10.38124/ijisrt20aug553
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Affect Attitude of Apps Developers to Comply with the Islamic Work Ethic in Developing an Islamic Mobile App

Abstract: The study empirically revealed the constructs that affect attitude of apps developers to comply with the Islamic Work Ethic in developing an Islamic mobile app. The Islamic Work Ethic (al-birr and Masuliyah) in this study was built based on the Mobile Apps Rating Scale (MARS) criteria, which are Engagement (EN), Functionality (FC), Aesthetics (AE) and Information (IN). This is mainly due to the lack of content authenticity and reliability, ideas in order to create interesting apps and the guidelines to the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The images used in apps should be relevant to the content and not display images that are not related to Islamic elements. The study [2] added that the application's selection buttons, icons, menus, and information should be of excellent quality and resolution to make it easier for viewers to understand and receive clear Islamic material. Furthermore, the final multimedia element that needs to be considered in developing apps for children with autism is sounds.…”
Section: Multimedia Elements (Religious Apps)mentioning
confidence: 99%
See 4 more Smart Citations
“…The images used in apps should be relevant to the content and not display images that are not related to Islamic elements. The study [2] added that the application's selection buttons, icons, menus, and information should be of excellent quality and resolution to make it easier for viewers to understand and receive clear Islamic material. Furthermore, the final multimedia element that needs to be considered in developing apps for children with autism is sounds.…”
Section: Multimedia Elements (Religious Apps)mentioning
confidence: 99%
“…Similarly, [3] reported that an application should use features that present the Islamic identity like using the mosque icon as a homepage button for the user. Meanwhile, [2] mentioned that in terms of information and distribution, an application layout is characterised by Islamic concepts. For instance, the application needs to display an ustaz icon for male voice selection and ustazah icon for female voice.…”
Section: Features Of Application (Religious Apps)mentioning
confidence: 99%
See 3 more Smart Citations